Penyesuaian Sosial Peran Ganda Mahasiswi Pasca Menikah - Surahmad, Peni Septiana, Dr. Eny Purwandari, M.Si (2016)
The newly married couple with marriage age under 5 years is an age prone to conflict because at this age there is a process of adjustment and the union of two individuals who have differences that would cause problems in the household, so that in the first year of married life need to make adjustments one each other as family. In addition, it is also necessary to the preparation and adjustment in their new roles such. Dual responsibility occurs when one or both of the couple undergo a period of study, where they have to divide their time between family and school, namely living, taking care of household chores and college. In fact a dual role gives serious consequences for the student. On the one hand, a student needs to carry out their duties for the study which he traveled and on the other hand, after getting married, the student should be able to carry out their responsibilities as wives and mothers. The purpose of this study was to understand and describe the dual role of social adjustment after the married student at Muhammadiyah University of Surakarta. In this study used two research methods, the method of ratting scale behavioral observation and interviews. There are six married couples who become informants with 4 couples who live together and the two couples who undergo long-distance relationship (Long Distance in Merriages). The results of this study are students who are married have a new role which, among others, as a housewife, his wife and daughter, and become full citizens. Social adjustment dual role that has been formed visible on the students who are married who only lives with her husband. this is because the student is already aware of the demands of the social environment that must be met.